Antifungal Starch–Gellan Edible Coatings with Thyme Essential Oil for the Postharvest Preservation of Apple and Persimmon - Sapper, Mayra; Palou, Lluís; Pérez-Gago, María B.; Chiralt, Amparo (MDPI, 2019)
Starch–gellan (80:20) coating formulations were applied to apples and persimmons to analyse their effectiveness controlling the weight loss, respiration rate, fruit firmness, and fungal decay during postharvest. Thyme essential oil (EO) was incorporated (0.25 and 0.5 g per g of polymer) directly or encapsulated in lecithin to enhance antifungal action. Coatings did not reduce weight loss or firmness changes in apples, but they prevented water loss in persimmons. In contrast, no significant effect of the coatings was observed on the respiration rates and the respiration quotient of persimmons, whereas the respiration rates and quotient was increased in apples. On the other hand, the coatings without lecithin reduced the incidence and severity of black spot caused by Alternaria alternata in persimmons, regardless of the content of essential oil. Likewise, these reduced the severity of gray mold caused by Botrytis cinerea in apples. No positive effect of lecithin in coatings was observed on the postharvest quality and decay in either apples or persimmons, nor did EO exert antifungal action despite its proven effectiveness in in vitro tests.